Research on Dynamic Performance and Wheel Damage of Metro Vehicle with Radial Bogie - Jincheng LI; Junjun DING; Yang YANG; Pengpeng WU; Fu LI (机车电传动)
In order to study the dynamic performance of metro vehicles, the steering principle of radial mechanism was analyzed, three dynamic models of metro vehicles were established, which were traditional, self-steering and forced-steering and according to the wheel rolling contact fatigue damage model, the wheel damage of vehicle passing curve was calcalated. The results showed that the radial mechanism of the vehicle strengthened the connection between the vehicle components and optimized the stability and lateral smoothness of the vehicle, the forced-steering vehicle had a greater advantage in curve operation, and all the evaluation indexes were better than the self-steering vehicle. When the three vehicle models run on the same line, the wheel damage of the forced-steering vehicle was the smallest, which was only 21% of the traditional metro vehicle wheels when the curve radius was 300 m. The damage of the self-steering vehicle and the traditional vehicle wheels was greater, and the damage of the self-steering vehicle wheels was less than the traditional vehicle wheels with the increase of the curve radius. So, the installation of forced steering mechanism for metro vehicles could effectively reduce the wheel rail interaction force and reduce wheel damage.